Eficiência de três métodos : alternativo, biológico e químico, no controle do ácaro Varroa destructor Anderson e Trueman (2000) em Apis mellifera Linnaeus (1758) - Pérez, Brenda Rubi Bautista (2016)
Bees are the most important pollinators of agricultural ecosystems by carrying out pollination of up to 90% of native plants and more than one third of cultivated plants. Studies conducted around the world have been demonstrating a phenomenon called CCD (Colony Collapse Disorder), whose causal agent several factors including diseases that affect this group. Among them, the varroa resulting from the Varroa destructor mite attack, is reported as pathogen major impact factor on the Apis mellifera. In view of this, the objective of this study was to test the efficiency of three methods to control V. destructor: alternative, obtained from the distillation of oregano (Origanum vulgare Linnaeus, 1753), thyme (Thymus vulgaris Linnaeus, 1753) and sugar beet (Beta vulgaris Linnaeus, 1753); biological, run base drones and larvae chemical, carried out with the application of active flumethrin principle. The results were evaluated by statistical analysis in R program to determine the differences between treatments and proposed mergers and select the best method of control. In the analysis, it was observed that the alternative method showed a significant difference by highlighting thyme distillation as more efficient because there is no significant killing of bees and cause the death of all the mites in a shorter time compared to the other distillates. The biological method hornets larvae base is also preferably effective due to mite in these individuals. In chemical control the use of the active ingredient flumethrin caused poisoning in bees, with diarrhea in the first 6 hours after application, and after 48 hours caused a mortality of 100%, which demonstrates be impractical to control the mite.